The TOOW model applied to high education teachers - Ferreira, Maria João (2021)
Nowadays digital technologies are having an impact on the transformation, so called Digital Transformation (DT), of society, organizations and economy even more profound and more widespread than any other transformation that occurred in history. Social media tools represent a subset of these technologies that contribute to the digital transformation of organizations and that are already used within organizational training contexts. However, the adoption of social media tools alone does not guarantee such a transformation; changes in the culture and behaviour of the higher education organization are also necessary. Taking advantage of facilitators of DT technology and realizing the need for updated approaches to address the training of higher education teachers, we propose the use of a model to guide teachers training within DT. The model to be used, called Training of Organizational Workers (ToOW), addresses the 2nd layer of the mobile_Create, Share, Document, Improve and Training (m_CSDIT) framework. In this paper, a case study will be presented in which the Training of Organizational Workers model will be applied to High Education Teachers.